Synthesis of novel benzoxazine having vinyl group and copolymerization with vinyl monomers. - Takeichi, Tsutomu (Asean Engineering Journal)
A novel benzoxavine having vinyl group, namely P-4va, was prepared from phenol, formaldehyde and 4-vinylaniline. The chemical structure of P-4va was confirmed by FT-IR and H NMR analyses. The polymerization behavior was investigated by differential scanning calorimetry (DSC). Exothermic peak of P-4va appeared at 209 degree celcius in the DSC measurement due to the chain polymerization of the vinyl group and the ring-opening of benzoxavine, which occured at the same temperature range. Thermal cure of P-4va afforded PP-4va that has glass transition temperature (Tg) at 244 degree celciuus and char yield above 48 percent, exhibiting that the thermal properties of PP-4va is higher than those of a typical polybenzoxavine without vinyl group. Radical polymerization of P-4va and copolymerization with styrene (St) and methyl methacrylate (MMA) were carried out using 2,2'-azobisisobutyronitrile as the initiator, affording homopolymer and copolymers bearing benzoxavine units as the pendant. Further heat treatment of the copolymers at 240 degree celcius afforded cured copolymers with Tg above 300 degree celcius and high char yield, indicating that the copolymers serve as high-molecular weight precursors of polybenzoxavine.